RENAL MICROPERFUSION RESPONSE TO A COLD PRESSURE TEST IS DECREASED IN HYPERTENSIVE PATIENTS. (June 2022) - Hendriks-Balk, Mariëlle; Damianaki, Aikaterini; Polychronopoulou, Erietta; Brito, Wendy; Pruijm, Menno; Wuerzner, Grégoire
Abstract : Objective: Microcirculation is essential to supply oxygen and nutriments to tissue. Alteration in the microcirculation is often proposed as a mechanistic link between hypertension and target organ damage. The recent developments in contrast-enhanced ultrasonography (CEUS) have enable the quantification of renal microcirculation. The objective of this study was to compare the microcirculatory response during a cold pressure test (CPT) in hypertensive (HT) patients with those in healthy normotensive (NT) participants. Design and method: This was a prospective case-control study. Hypertensive (HT) and normotensive (NT) participants underwent two separate CPT of 2 minutes. Doppler ultrasound was used to measure renal resistive index (RRI) and CEUS to measure the perfusion index (PI) as a proxy of renal tissue microcirculation. Renal Doppler and CEUS were performed before and during the CPT. We compared baseline measures and responses to CPT of HT and NT groups using a Wilcoxon test. Results: Sixteen hypertensive and nineteen normotensive male participants were included. HT participants were older and had higher blood pressure and body mass index. Baseline RRI was similar in both group, but HT had lower PI (median with interquartile range): 1083 U(447–1476) vs 1772 U(1295–2557), p = 0.016. The CPT decreased the RRI in NT and increased the RRI in HT, resulting in a different CPT response -0.026 [CI -0.045; -0.008, p = 0.006]. The CPT increased the PI in both groups but the response was blunted in HT patients - 755U ± 518, (p = 0.01). Conclusions: Compared to healthy participants, hypertensive patients show a paradoxal RRI response and a lower increase in perfusion index during CPT suggesting that microcirculation and possibly renal autoregulation is altered. This is the first demonstration showing that CEUS enables the detection of microcirculatory differences between healthy participants and hypertensive patients.